Design and development of automatic Droplet System for Core-Shell Quantum Dot Synthesis - Nugraha, Olland; Asnil (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The gradual and precise addition of solution is a critical factor in the synthesis of core–shell quantum dots. Manual dripping poses a risk of inaccuracy in both volume and timing, thus an automated system capable of operating stably and programmatically is required. This research aims to design and develop an automatic solution dropping system based on an Arduino Uno microcontroller and a servo motor combined with gear and rack mechanisms. The system is designed to control both the volume and timing of the droplets, with selectable intervals tailored to the synthesis requirements. The main components used include a syringe, servo motor, gears and rack gear as mechanical actuators, along with an LCD and buzzer as user interface and status indicators. Test results show that the system operates automatically according to the set time and can deliver solution droplets with consistent volume. This device is expected to enhance the synthesis process of quantum dots by increasing efficiency, precision, and minimizing manual intervention